To advance the Gospel : New Testament studies - Fitzmyer, Joseph A (1998)
"In this greatly expanded second edition of To Advance the Gospel, Joseph Fitzmyer has added eight new studies of important Pauline and Lucan topics not part of his original work. Together these nineteen essays consider a number of major issues in the study of the New Testament as well as in the life of the church today
Readers will find discussions of such themes as the priority of Mark and the "Q" source in Luke, crucifixion in ancient Palestine, the gospel in the theology of Paul, the ascension of Christ and Pentecost, and the resurrection of Christ according to the New Testament."--Jacket
I. Gospel Topics. 1. The Priority of Mark and the "Q" Source in Luke. 2. The Virginal Conception of Jesus in the New Testament. 3. The Matthean Divorce Texts and Some New Palestinian Evidence. 4. Aramaic Kepha and Peter's Name in the New Testament. 5. Crucifixion in Ancient Palestine, Qumran Literature, and the New Testament -- II. Pauline Topics. 6. The Gospel in the Theology of Paul. 7. Reconciliation in Pauline Theology. 8. Paul and the Law. 9. "To Know Him and the Power of His Resurrection" (Phil 3:10). 10. New Testament Kyrios and Maranatha and Their Aramaic Background. 11. Habakkuk 2:3-4 and the New Testament -- III. Lucan Topics. 12. Jesus in the Early Church through the Eyes of Luke-Acts. 13. The Ascension of Christ and Pentecost. 14. The Use of the Old Testament in Luke-Acts. 15. The Designations of Christians in Acts and Their Significance. 16. "A Certain Sceva, a Jew, a Chief Priest" (Acts 19:14) -- IV. Further Pauline Topics
Includes bibliographical references and indexes
Keywords: Bible. -- Criticism, interpretation, etc; BIBLE (NT) -- Criticism, interpretation, etc; Criticism, interpretation, etc; Aufsatzsammlung